Comparative evaluation of gingival depigmentation by tetrafluroethane cryosurgery and surgical scalpel technique. A randomized clinical study - Suraj D Narayankar; Neeraj C Deshpande; Deepak H Dave; Dhaval J Thakkar (Wolters Kluwer Medknow Publications, 2017)
Introduction: Importance of good smile cannot be underestimated in enhancement of beauty, self-confidence and personality of a person. Health and appearance of gingiva is an essential part of attractive smile. Gingival pigmentation gives rise to unesthetic smile line. In present world, with increasing awareness to esthetic, people have become highly concerned about black gums. Various treatment modalities like abrasion, scrapping, scalpel technique, cryosurgery, electrosurgery and laser are available for treatment of gingival pigmentation. The present study was conducted with an objective of comparing efficacy of gingival depigmentation by cryosurgery and scalpel technique. Method: A Randomized control split mouth study was conducted for 25 patients with gingival pigmentation. Gingival pigmentation Index (GPI) for pigmentation and Visual Analoug Scale (VAS) for pain was evaluated for both test (Cryosurgery) and control sites (Scalpel technique) at baseline, 1month, 3months and 6 months. Results: GPI score was 3 and 2 for 21/25 and 4/25 control sites and was 22/25 and 3/25 test sites respectively at baseline. Both the groups showed significant reduction in GPI score i.e., 0 at 1 and 3 months interval after treatment. GPI score increased to 1 for 5/25 sites treated with scalpel technique and 2/25 sites treated with cryosurgery at 6 months interval (P=0.0691). This indicates recurrence rate for pigmentation is higher after scalpel treatment. VAS Score was 3 for 10/25 sites treated with scalpel and was 2 for 12/25 sites treated with cryosurgery (P<0.001). Conclusion: It can be concluded that cryosurgery can be effectively and efficiently used for depigmentation by keeping patients acceptance and comfort in mind and also the long term results and ease of use when compared to scalpel technique.